Итак:
а₁ = -3
d = 1 - очевидно из условия, что каждый последующий член на 1 больше предыдушего.
По формуле суммы:
S₂₀ = (2a₁ + d(20-1))*20/2 = (-6 + 19)*20/2 = 130
a1=-3
d=-2-(-3)=-2+3=1
a(n)=-3+1*(n-1)=n-4
a(20)=20-4=16
S(20)=((-3+16)/2)*20=13*10=130
Итак:
а₁ = -3
d = 1 - очевидно из условия, что каждый последующий член на 1 больше предыдушего.
По формуле суммы:
S₂₀ = (2a₁ + d(20-1))*20/2 = (-6 + 19)*20/2 = 130
a1=-3
d=-2-(-3)=-2+3=1
a(n)=-3+1*(n-1)=n-4
a(20)=20-4=16
S(20)=((-3+16)/2)*20=13*10=130